Mohammed Althubaiti, the Prometheus of Poets: "A Reading of Ali Alnahawi’s Poem "The Desert Maser - Al-Ahmadi, Majdi bin Eid; Al-Dosari, Mohammed bin Abdullah (Al-Adab Journal, 2023)
The present study aims at showing the position of the poet Mohammed Althubaiti as described in Ali Alnahawi’s poem titled "The Desert Maser" which appeared in The Female of the Dice collection. This poem represents Alnahwi’s belief in the distinctive position of Muhammad Althubaiti in poetry and in recognition of his artistic status. Accordingly, this study came to explore this poem, focusing on its title, structure, as well as the deep connotations and textual intersections prevailing in it. The study gains importance in dealing with a text that highlights the impact of the poet Muhammad Al-Thubaiti, who is considered the most prominent poets of Saudi Arabia even after his death, Because of his enlightening influence on the poets of his generation and those after them.He was born in 1952 in the city of Taif. He is considered one of the pioneers of activating poetry, and has won a number of awards, including: the award for the best poem in the seventh session of the Foundation of the Abdul Aziz Saud Al-Babtain Prize for Poetic Creativity, in 2000, for the poem (The Position of the Sand.. The Position of Alliteration), and the award and title (Okaz Poet), In 2007, Al-Thubaiti suffered a heart attack, after returning from a cultural trip to Yemen, which he suffered from its effects for a long time, until he died - may God have mercy on him - on Friday, January 14, 2011. The al-Thubaiti poet has several collections of poetry, and the Literary Club in Hail has published the complete al-Thubaiti poetic works in one volume. The study concluded by revealing a text that expresses admiration for the personality of Mohammed Althubaiti. Remarkably, Ali Alnahawi goes beyond the usual and the familiar for praise poems by recognizing Mohammed Althubaiti’s uniqueness in the field of poetry which brings him out of the world of the merely great poets to the world of the legendary characters. Outstandingly, Ali al-Nahwi bestows on al-Thabiti qualities of a miraculous and legendary dimension, which is manifested in his belonging to the wind that gives him dominion over the hand, which makes the text place the recipient in front of a character who tends to legend.